New Approach of Vector ECG Analysis for Revealing Coronary Artery - Bastys, A.; Blužas, J.; Kaminskienė, S.; Navickas, R.; Urbonavičienė, G. (Elektronika ir Elektrotechnika, 2004)
A vector ECG parameters based computer prognosis of coronary artery stenosis and ischaemic heart diseases is proposed. Averaged vector ECG is described by 29 geometrical parameters that are independent on the heart axis. Classification is made by multiple logistic regression method. Classification parameters are defined by a training set of 195 patients; classification is verified on test set containing 55 patients. Classification results performed using vector ECG and 12 lead ECG parameters were compared. As distinct from earlier authors, new method didn′t mark overtraining problem. Ill. 3, bibl. 8 (in English; summaries in Lithuanian, English and Russian).